2020
DOI: 10.1021/acs.orglett.0c00081
|View full text |Cite
|
Sign up to set email alerts
|

Halogen-Bond-Induced Consecutive Csp3–H Aminations via Hydrogen Atom Transfer Relay Strategy

Abstract: The utilization of a halogen bond in a number of chemical fields is well-known. Surprisingly, the incorporation of this useful noncovalent interaction in chemical reaction engineering is rare. We disclose here an uncommon use of halogen bonding to induce intermolecular Csp 3–H amination while enabling a hydrogen atom transfer relay strategy to access privileged pyrrolidine structures directly from alkanes. Mechanistic studies support the presence of multiple halogen bond interactions at distinct reaction stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 79 publications
1
31
0
Order By: Relevance
“…The investigation of halogen bonding in the solution‐phase has lagged behind considerably, although recent applications, [16–18] fundamental studies [19] and receptor anion transport have been reported in the last decade [20,21] . The utility and importance of halogen bonding is now growing in recognition in the organic synthesis communities, whereby halogen bonded complexes have been used as reagents [22] and the Lewis acidic nature of electrophilic halogen reagents has been used to activate reactions or even initiate catalytic events [23–30] . Indeed, we became intrigued by the halogen bonding nature of the electrophilic reagents NIS and NBS that are commonly used in catalytic halo‐functionalizations, specifically their mechanistic role and reactivity in the halo‐cyclization of γ‐olefinic alcohols and acids in the presence of amine catalysts ( Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of halogen bonding in the solution‐phase has lagged behind considerably, although recent applications, [16–18] fundamental studies [19] and receptor anion transport have been reported in the last decade [20,21] . The utility and importance of halogen bonding is now growing in recognition in the organic synthesis communities, whereby halogen bonded complexes have been used as reagents [22] and the Lewis acidic nature of electrophilic halogen reagents has been used to activate reactions or even initiate catalytic events [23–30] . Indeed, we became intrigued by the halogen bonding nature of the electrophilic reagents NIS and NBS that are commonly used in catalytic halo‐functionalizations, specifically their mechanistic role and reactivity in the halo‐cyclization of γ‐olefinic alcohols and acids in the presence of amine catalysts ( Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…N−I bond‐assisted intramolecular substitution then leads to the formation of the cyclic sulfamide 2 along with the generation of I 2 . It appears that the presence of N−I bond is essential to promote this substitution step, but the details regarding the mechanism remain unclear [26,27] …”
Section: Methodsmentioning
confidence: 99%
“…NMR data were in agreement with the literature data. [29] N-(tert-butyl)-2-methylbenzenesulfonamide (3j)…”
Section: -Methoxy-n-(1-phenylethyl)benzenesulfonamide (3i)mentioning
confidence: 99%